2021
DOI: 10.3390/mi12050561
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Optimization of Piezoelectric Energy Harvesters via Pattern Search Algorithm

Abstract: A data-driven optimization strategy based on a generalized pattern search (GPS) algorithm is proposed to automatically optimize piezoelectric energy harvesters (PEHs). As a direct search method, GPS can iteratively solve the derivative-free optimization problem. Taking the finite element method (FEM) as the solver and the GPS algorithm as the optimizer, the automatic interaction between the solver and optimizer ensures optimization with minimum human efforts, saving designers’ time and performing a more precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…On the other hand, a study with geometry ratio optimization [35] obtained a slightly higher power density than this study. In addition, very high power density was obtained in study that optimized geometry by using power density as the objective function of optimization [36]. The difference between the previous two studies and this study is consideration of discrete variables and stress constraints.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…On the other hand, a study with geometry ratio optimization [35] obtained a slightly higher power density than this study. In addition, very high power density was obtained in study that optimized geometry by using power density as the objective function of optimization [36]. The difference between the previous two studies and this study is consideration of discrete variables and stress constraints.…”
Section: Resultsmentioning
confidence: 83%
“…Through comparison, it can be confirmed that designs derived through optimization give better results than designs based on empirical intuition. Meanwhile, in the study that showed the highest power density [36], power density was used as the objective function. The point to note here is that it is true that an efficient PEH design with high power density was performed, but it cannot be said that the amount of power is maximum in a given space.…”
Section: Resultsmentioning
confidence: 99%
“…Thereupon, optimization was performed to boost the total output power which was significantly higher than that of a single piezoelectric energy harvester. Huang et al [5] proposed an automatic data-driven strategy to optimize the design of piezoelectric energy harvesters, based on the algorithm of generalized pattern search (GPS), which can effectively save designers' effort and achieve more precise parameters. Employing the optimal length and thickness, the derived energy harvester showed an increment of 371% and 1000% in output power and normalized power density, respectively.…”
mentioning
confidence: 99%